PEMBERDAYAAN KOMUNITAS: STEM UNTUK PEMBELAJARAN MATEMATIKA MENYENANGKAN - Fina Hanifa Hidayati; Aflich Yusnita Fitrianna; Rima Aksen Cahdriyana (Jurnal Penamas Adi Buana, 2023)
Learning abilities that are elements of learning in the 21st century require teachers to have skills in guiding students to develop communication skills, process information, think creatively, solve problems, collaboration and manage themselves. These abilities can be developed through the implementation of innovative learning in the classroom, one of which is the STEM approach. STEM-based learning integrates four fields, namely science, technology, engineering and mathematics in one learning activity. This service activity was carried out by 30 mathematics teachers who were members of the Mathematics teacher community in Denpasar City. The activity is carried out using the Asset Based Community Development (ABCD) method. The service activities that have been carried out have a good impact on teachers. At the end of the activity, teachers can understand STEM-based mathematics learning through practical learning activities and are able to develop learning innovations by compiling STEM-based learning scenarios.